Functional Consequences of the Evolution of Matrimony, a Meiosis-Specific Inhibitor of Polo Kinase - Bonner, Amanda M (Mol Biol Evol, 2019)
Meiosis is a defining characteristic of eukaryotes, believed to have evolved only once, over one billion years ago. While the general progression of meiotic events is conserved across multiple diverse organisms, the specific pathways and proteins involved can be highly divergent, even within species from the same genus. Here we investigate the rapid evolution of Matrimony (Mtrm), a female meiosis-specific regulator of Polo kinase (Polo) in Drosophila. Mtrm physically interacts with Polo and is required to restrict the activity of Polo during meiosis. Despite Mtrm’s critical role in meiosis, sequence conservation within the genus Drosophila is poor. To explore the functional significance of this rapid divergence, we expressed Mtrm proteins from 12 different Drosophila species in the Drosophila melanogaster female germline. Distantly related Mtrm homologs are able to both physically interact with D. melanogaster Polo and rescue the meiotic defects seen in mtrm mutants. However, these distant homologs are not properly degraded after the completion of meiosis. Rather, they continue to inhibit Polo function in the early embryo, resulting in dominant maternal-effect lethality. We show that the ability of Mtrm to be properly degraded, and thus release Polo, is partially due to residues or motifs found within Mtrm’s least-conserved regions. We hypothesize that, while Mtrm regions critical for its meiotic function are under strong purifying selection, changes that occurred in its unconserved regions may have been advantageous, potentially by affecting the timing or duration of meiosis and/or the early embryonic divisions.